The development of chrome free chestnut and Tetrakis Hydroxymethyl Phosphonium Sulfate based Eco-benign combination tanning system - Haftom Girmay; Ashagrie Mengistu; Berhanu Assefa; Mikiyas Abewaa; Getaneh Andualem; Bereket Yeheyis (Heliyon, 2024)
The replacement of the conventional chromium tanning system with an eco-benign tanning systems has received great attention owing to stringent environmental regulations. In this specific study, a chrome-free combination tanning system based on chestnut and tetrakis (hydroxymethyl) phosphonium sulfate (THPS) was developed and presented as an effective alternative cleaner tanning technology. Processing of the tanning trials were carried out varying the percentages of chestnut as a tannage, followed by THPS as a re-tannage for process optimization. The leathers obtained were characterized for their thermal stability, grain surface properties using a scanning electron microscope, physical strength characteristics, comfort, and organoleptic properties. Finally, the environmental impact of the tanning systems was assessed through the comparative analysis of their spent liquors. The chestnut-THPS combination system tanned leathers using 20 % chestnut followed by 2 % THPS resulted in maximum shrinkage temperature of 95OC. The hydrothermal stability of the leathers tanned using this combination tanning system were found to be better than those tanned using chestnut and THPS tanning systems alone, respectively. The strength and comfort properties of the leathers produced using the developed combination tanning system were found to be on par with or better than those of conventionally tanned leathers, and the scanning electron microscopic study depicted that the grain surface of the leathers produced were observed to be free of surface deposition. The environmental impact assessment showed that the combination tanning system used resulted in a significant reduction in TS, TDS, TSS, and BOD in the wastewater. This research article has attempted and established the use of chestnut-THPS-based combination tanning systems as an effective, eco-friendly alternative tanning process technology.